PERKEMBANGAN AGAMA ISLAM DARI TRADISI SENI WAYANG KULIT DI KOTA MADIUN - Aditya Chandra Abdullah; Budi Harianto (HUMANISTIKA : Jurnal Keislaman, 2023)
Da’wah is also the duty of a Muslim. In preaching, of course, a Muslim needs a medium to convey what will be conveyed. In this millennial era, preaching can be done anywhere, especially on social media, arts, traditions, even the Wayang Kulit tradition. However, in some areas, wayang kulit has begun to decline in development and its existence has dwindled, but in some areas there are still puppet shows, for example in the city of Madiun. Da’wah strategy conveyed by the Dalang figure from a conversation from a wayang play being played. In a wayang play, there are philosophies that can describe Islamic terms. This was also conveyed by the Dalang using language that the public could easily understand. Wayang kulit was chosen as the most effective medium of propaganda because wayang is also part of Javanese culture, which is still favored by various groups of Javanese society. And also the stories or plays in Wayang also contain Islamic teachings.